Aggrecanases in cartilage matrix breakdown - Nagase, H (2001)
In rheumatoid arthritis and osteoarthritis, the loss of extracellular matrix macromolecules, aggrecan and collagens exceeds new production, resulting in serious joint impairment. The primary cause of this loss is due to elevated proteolytic enzyme activities. Recent studies have suggested that the enzymes called 'aggrecanases' that specifically cleaves the Glu373-Ala 274 of the aggrecan core protein play a key role in the early phase of cartilage destruction. Two aggrecanases have been purified and cloned, they are designated as ADAM-TS4 and ADAM-TS5, subfamily members of the ADAM family. Recombinant ADAM-TS4 and ADAM-TS5 effectively cleave the core protein of native aggrecan, but they have little action on other protein substrates.